Peningkatan Hasil Belajar Peserta Didik dengan Metode Pembelajaran Berbasis Masalah - Choirun Nisa; Agit Purwo Hartanto; Prawita Kartika Sari (STKIP Andi Matappa Pangkep, 2023)
This research is motivated by observational data which shows the acquisition of student learning outcomes on thematic material is low. To respond to this, researchers apply a problem-based learning model that aims to improve the learning process and student learning outcomes. This research was conducted in fourth grade at Al-Akhyar Islamic Elementary School, East Jakarta. This research is a classroom action research model by Kemmis and Mc. Taggart. Data collection techniques using interviews, observation, and also documentation. The results of the study showed that after applying the problem-based learning model for two cycles there was a significant increase in learning outcomes.